Community‐acquired invasive Staphylococcus aureus: Uncovering disparities and the burden of disease in Auckland children. (29th July 2019) - Vogel, Alison M; Borland, Annie; van der Werf, Bert; Morales, Adrienne; Freeman, Joshua; Taylor, Susan; Anderson, Phillipa; Horsfall, Maraekura; Drinkovic, Dragana; Lennon, Diana R
Abstract : Aim: Staphylococcus aureus (SA) causes serious invasive disease in children. Large studies have measured the incidence of SA bacteraemia, but there is less information on the total burden of community‐acquired invasive SA (iSA) in children. Methods: A retrospective, cross‐sectional analysis of Auckland resident children aged 0–14 years who were hospitalised with iSA between 2011 and 2015 was performed. Laboratory databases and SA‐related international classification of diseases 10 discharge codes were searched to identify community‐onset cases with SA isolated from a normally sterile site. Clinical records and coroner's reports were reviewed to determine clinical syndromes and exclude nosocomial infections. Results: A total of 295 children with iSA were identified. The average annual incidence of iSA was 18.6 per 100 000 – for Pacific populations 44.3 per 100 000, Māori 24.3 per 100 000 and New Zealand European and other 8.8 per 100 000; 68% had bacteraemia. The incidence of iSA for Pacific infants was 10 times greater than non‐Māori/non‐Pacific (113.4/100 000 population vs. 11.8/100 000). Multivariate analysis found a higher risk of admission in Pacific children, males and those living in areas of high deprivation. Thirty‐two patients (10.8%) were admitted to the intensive care unit; risk was higher in infants, Pacific children and those with respiratory infection (Relative Risk (RR) 12.2, 95% confidence interval (CI) 5.7–26.4) and multifocal (RR 6.9, 95% CI 3.4–13.8) and endovascular disease (RR 8.9, 95% CI 3.9–20.6). All deaths ( n = 7) had respiratory infections, and four were patients <1 year of age. Conclusions: Studies investigating SA bacteraemia alone significantly underestimate the total burden of iSA disease. There are marked ethnic and socio‐economic disparities in iSA disease among Auckland children. Pacific infants are at the highest risk.